Persons deprived of liberty in Ecuador: an unexplored suspect classification? - Espinoza Guillén, Bairon Iván (USFQ Law Review, 2023)
The development of doctrine regarding suspect classification has contributed to the fact that several distinctions, prohibited from discrimination, are recognized with this status. However, on the distinction of deprivation of liberty of a person, there is no pronouncement. The main objective of this thesis is to analyze, from a critical approach, whether such a distinction deserves to be recognized as a suspect class. For this, a deductive method was used, which deepened the jurisprudential criteria of the suspect classification protected by a jus cogens norm and a recent restrictive-differentiating measure implemented in the penitentiary system. The analysis concludes by stating that the distinction of deprivation of liberty does not exceed the standards for this recognition, because if this quality or status were granted, it would complicate the exercise of configurative freedom of the penal norm, which in the future would generate unconstitutional normative satisfactions that would hardly overcome the strict scrutiny test.